Analisis Manajemen Sarana dan Prasarana di SMAN 7 Binjai - Putri Sinaga; Tri Wandani Lase; Nasha Astrid Syahfitri; Adeline Adeline; Eni Yuniastuti (Journal on Education, 2024)
Education is one of the important pillars in building a nation and state. In this era of globalization, education is the main key in increasing the nation's competitiveness (Darsiah, 2018. To achieve the goal of quality education, adequate facilities and infrastructure are needed. Educational facilities and infrastructure are a very important supporting factor in the teaching and learning process, because without If there are educational infrastructure, the education and learning process will not run optimally (Susanti, 2016). The aim of this research is to determine the condition of facilities and infrastructure at SMAN 7 Binjai, to determine the form of management of educational facilities and infrastructure in supporting existing student learning activities. at SMAN 7 BINJAI, to find out what problems occur in the management of facilities and infrastructure at SMAN 7 BINJAI Location This research was carried out at SMAN 7 which is located at Jalan Sawi no. 48 Paya Roba Binjai, Paya Roba, West Binjai District Prov. North Sumatra. The research method uses a qualitative approach aimed at knowing or describing the reality and events being studied by describing them in words and language in a natural context using various scientific methods. Apart from that, it uses observation, interviews and documentation methods. The results of this research are that the storage and maintenance of facilities and infrastructure at SMAN 7 Binjai school is carried out together with all members of the school environment so that they are used properly, but in this case there is still someone responsible for the facilities at the school so that they can be used as well as possible, for example if someone borrows the item, this will be done record keeping so that there is no loss of goods or damage to goods.